Be positive - Moss, Mariam (Hove Wayland, 1992)
From the STAYING HEALTHY series, a guide to physical and mental health, with advice on diet, exercise, sleep, relaxation, and how to recognise and deal with stress. Illustrated with colour photographs and artwork.